Managing the environmental problems of irrigated agriculture through the appraisal of groundwater recharge. (September 2018) - Singh, Ajay
Highlights: Environmental problems of salinisation and waterlogging are evaluated. The process dynamics of the environmental problems are analysed. The enhanced agricultural practices and changed cropping are suggested. The recommended policies achieve long-term social goals of environment protection. Abstract: This study employed an easy groundwater recharge model which requires input values that are effectively on hand or attainable and exactly measured. The estimated long-term seasonal groundwater recharges have been used for the assessment of environmental issues of agricultural lands in an irrigated semiarid area of northwest India, where groundwater level has risen. The groundwater recharge model performed very nicely in calculating the watertable depths in the course of the entire study period (1996–2016) which is also substantiated statistically through the lower values of root mean squared error (0.2133 m) and mean error (−0.0325 m) and high model efficiency (0.88) and regression coefficient (0.979). Various scenarios have been studied to look at the impact of model's input variation on its output. The analysis of various recharge components shows an average annual watertable rise of 0.08 m in the command due to a higher positive average net recharge in the monsoon season which cannot be fully counterbalanced by a lower negative mean net recharge during the winter season. Among the scenarios analyzed, the better agricultural practices with modified cropping pattern have delivered the best effects for containing the environmental issues of salinization and waterlogging.